Monetary Policy and COVID-19 - Brzoza-Brzezina, Michal; Kolasa, Marcin; Makarski, Krzysztof (Washington, D.C. : International Monetary Fund, 2021)
We study the macroeconomic effects of the COVID-19 epidemic in a quantitative dynamic general equilibrium setup with nominal rigidities. We evaluate various containment policies and show that they allow to dramatically reduce the welfare cost of the disease. Then we investigate the role that monetary policy, in its capacity to manage aggregate demand, should play during the epidemic. According to our results, treating the observed output contraction as a standard recession leads to overly expansionary policy. Finally, we check how central banks should resolve the trade-off between stabilizing the economy and containing the epidemic. If no administrative restrictions are in place, the second motive prevails and, despite the deep recession, optimal monetary policy is in fact contractionary. Conversely, if sufficient containment measures are introduced, central bank interventions should be expansionary and help stabilize economic activity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: General Aggregative Models; Health; Macroeconomic Policy and Macroeconomic Aspects of Public Finance; Monetary Policy, Central Banking, and The Supply of Money; National Government Expenditures and Related Policies